2013
DOI: 10.1136/jramc-2013-000165
|View full text |Cite
|
Sign up to set email alerts
|

Riot control agents: the tear gases CN, CS and OC—a medical review

Abstract: Introduction2-Chloroacetophenone (CN),o-chlorobenzylidene malonitrile (CS) and oleoresin capsicum (OC) are common riot control agents. While serious systemic effects are uncommon, exposure to high concentrations may lead to severe complications and even death. The aim of this narrative review is to summarise all main aspects of the riot control agents CN, CS and OC toxicology, including mechanisms of toxicity, clinical features and management.MethodsOVID MEDLINE and ISI Web of Science were searched for terms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 84 publications
0
38
0
13
Order By: Relevance
“…The decision by law enforcement to use tear gas during civil disorder is understandable, as CN, CS, and OC are effective RCAs and reduce the risk of injury to law enforcement personnel and demonstrators when used instead of physical force. 10,88 However, the massive increase in tear gas deployments worldwide, accompanied by advances in formulations and deployment technologies and the often-observed absence or disregard of evidence-based deployment rules and operating procedures, is of great concern. Epidemiological research on tear gas health effects is clearly deficient and has received little public support.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision by law enforcement to use tear gas during civil disorder is understandable, as CN, CS, and OC are effective RCAs and reduce the risk of injury to law enforcement personnel and demonstrators when used instead of physical force. 10,88 However, the massive increase in tear gas deployments worldwide, accompanied by advances in formulations and deployment technologies and the often-observed absence or disregard of evidence-based deployment rules and operating procedures, is of great concern. Epidemiological research on tear gas health effects is clearly deficient and has received little public support.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A 2003 analysis of several tear gases and incapacitants concluded that, on the basis of available toxicological evidence, commonly used tear gases have a large safety margin for life‐threatening or irreversible toxic effects . Another medical review published in 2013 concluded that, in the majority of exposures, significant clinical effects are not anticipated . However, there are debates surrounding the acceptability of tear gas use for riot‐control purposes, especially in the background of the recent massive use.…”
Section: Tear Gas Agents For Riot Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Several treatment options, including the use of nonsteroidal anti-inflammatory drugs (NSAIDs), are published for HD and CS tear gas-induced cutaneous injury, with mixed outcomes (8, 18, 19). Despite their use as chemical warfare agents more than a century, there is no specific antidote for sulfur mustard or tear gas agent-induced cutaneous injuries (9). Although some therapeutic agents were tested for SM and CS tear agent-induced injuries, symptomatic treatment is the general line of treatment (8, 9, 18, 20-23).…”
Section: Introductionmentioning
confidence: 99%
“…318,319,320 An examination by Toprak and colleagues of 10 deaths in which riot-control agents were either the principal or contributory cause of death, showed that 7 of the lethal cases were associated solely with a pepper spray product. 321 Most of the serious complications, however, resulted from exposure to very high doses, 322 or from the subject being very close to the spray, smoke, or exploding canister. 315 Pre-existing health conditions, such as asthma, COPD, or cardiovascular disease; or interaction with prescribed medications or illegal drugs may also influence the development of severe injuries.…”
Section: Capsicum (Pepper Spray)mentioning
confidence: 99%